The role of news content on Danish broadcasters' streaming services: A longitudinal content analysis of two video-on-demand services - Cores-Sarría, Lucia; Andersen, Mads Møller Tommerup; Heiselberg, Lene (Journalistica, 2024)
Amidst the shift from linear TV to streaming, public-service media face the challenge of reconciling commercial competition with their public obligation of informing society. This longitudinal content analysis investigates the curation and platformization of news on the front pages of the video-on-demand services of two Danish broadcasters, DRTV and TV 2 Play. Sampling four days annually from 2020 to 2022, we take a longitudinal approach to assess news curation (i.e., positioning and accessibility on the front page) and news platformization (i.e., video length, hard vs. soft news composition, and prevalence of streaming-first content). We did not find strong evidence of platformization overall. A main difference between the broadcasters was in terms of curation, with DRTV consistently prioritizing the news deck, while TV 2 exhibited a declining trend over time. This study contributes valuable insights into the treatment of news by broadcasters within the evolving context of streaming services.